How Finnish teachers understand multilingual learners’ language learning - Jenni Alisaari; Leena Maria Heikkola (Jyväskylän yliopisto, 2022)
The number of students whose home language is different from the language of instruction is growing everywhere. Learning a new language while simultaneously learning different subjects in that language, is challenging and requires teacher support. However, research has shown that not all teachers have sufficient knowledge of language learning, how language learning influences the learning of content, or how to support multilingual learners in this context (Sullivan, 2016). In this study, Finnish teachers’ (N = 820) understandings of certain processes related to learning an additional language were examined, including whether there were differences in understandings between different teacher groups. Over 80% of the surveyed teachers were knowledgeable about the aspects related to classroom interaction and language use that can be considered as essential for being a linguistically responsive teacher: for example, they knew that social interaction supports learners’ language development. In this study, the less experience a teacher had in general, the more knowledgeable they were regarding language learning. Further, teachers of language related subjects had a better understanding of certain aspects of language learning compared to other subject teacher groups. Based on these results, professional development targeted at teachers who have been in the profession for several years is recommended.